A Study of Glycosylated Hemoglobin (Hba1c) In Acute Coronary Syndrome - Sheetal D Vora; Kaushika S Chaudhary; Hardik K Parmar; Prashant J. Modi (Medsci Publications, 2016)
Background: In non diabetic patients, HbA1C could be utilised for risk stratification of CAD and its severity; independent of traditional cardiovascular risk factors. Objectives: To study the blood levels of HbA1C in patients of ACS at time of admission and its relation with early outcome and complications in ACS. Method- A total of 100 indoor patients without known diabetes, with confirmed diagnosis ofACS are included in study. HbA1C was done along with other routine investigations. Coronary Angiography was performed in all patients.  Results-Out of 44 patients with HbA1C value > 6.5%, 20(45.5%) had Anterior wall (A/W) MI, 15(34.1%) had Inferior wall(I/W) MI, 2(0.05%) had Lateral wall(L/W) MI, 5(11.4%) had NSTEMI and 1(0.02%) had UA. While of 56 patients with HbA1C value < 6.5%, 19(33%) had A/W MI, 18(32.1%) had I/W MI, 5(0.09%) L/W MI, 2(0.04%) had NSTEMI and 12(21.4%) had UA. Out of 88patients with normal RBS on admission,33 patientshad HbA1C > 6.5% i.e. in diabetic range. 31.8% of patients of raised HbA1C had complicated MI while complication rate in normal HbA1C group was 14.3% only. Conclusion- Patients with high HbA1C levels were associated with more severe disease and complication rate was also higher.